Psychological Research in the North - Berry, J.W. (Anthropologica, 2022)
A review is made of recent psychological research, carried out mostly in Canada, with northern native peoples. Organized in four sections, the review covers perceptual and cognitive skills, attitudes and values, personality traits and psychological response to acculturation. A final section provides an examination of the role of the psychologist in investigating and guiding the process of development in the North, and suggests some research topics which are urgent and essential if balanced development is to take place.